Neuroprotective effects of estradiol in hippocampal neurons and glia of middle age mice. - Saravia, Flavia Eugenia (2007)
During aging the hippocampus experiences structural, molecular, and functional alterations. Protection from age-related disorders is provided by several factors, including estrogens. Since aging defects start at middle age, we studied if 17 beta-estradiol (E(2)) protected the hippocampus at this age period. Middle age (10-12 month old) male C57Bl/6 mice were implanted sc with E(2) (15 microg) or cholesterol pellets. Ten days afterwards they received bromodeoxyuridine (BrdU) 4 and 2h before killing to study cell proliferation in the dentate gyrus (DG). A pronounced depletion of BrdU+cells in the DG was found in cholesterol-treated middle age mice, accompanied by astrocytosis, and by neuronal loss in the hilus. Middle age mice receiving E(2) showed increased number of BrdU+cells while the other parameters were remarkably attenuated. When steroid treatment was prolonged for 2 months to study migration of cells in the granular layer of the DG, cell migration was unaffected by E(2). However, E(2)-treated middle age mice presented higher cell density and increased staining for doublecortin, a marker for differentiating neurons. Thus, from the three basic steps of adult neurogenesis (proliferation, migration, and differentiation), E(2) stimulated progenitor proliferation - even after long exposure to E(2) studied by Ki67 immunocytochemistry - and differentiation towards a neuronal lineage. This result, in conjunction with recovery from other aging indicators as increased deposits of the aging pigment lipofuscin in DG cells, loss of hilar neurons and astrocytosis supports a wide range protection of hippocampal function of middle age mice by estrogenic hormones.